EMPIRICAL STUDY DALAM MENINGKATKAN SEMANGAT KERJA KARYAWAN PT EDS MANUFACTURING INDONESIA BALARAJA-TANGERANG - Fifi Oktaviani; Syaechurodji Syaechurodji; Abdul Wahid Alfarizi; Didit Haryadi (Jurnal Manajemen dan Bisnis, 2023)
Organizations can achieve success through their resources, especially human resources. Therefore, employees become the driving force in making a real contribution to the success of the organization on an ongoing basis. Of course, only employees with optimal work spirit can achieve this success. However, to maximize employee performance, there must be a strategy to improve it. This study aims to find out how these strategies improve morale. The PLS-SEM approach was used in this study. The results of this study indicate that organizational communication as well as the work environment can be a driver in the strategy of increasing employee morale, either directly or indirectly optimally through the work environment